Structuring Roman History: the Roman Year and the Roman Consular Tradition - Rich, John (Histos, 2011)
This article is concerned with the shaping of the annual narrative in historical writers working in the Roman annalistic tradition and contests the view that Livy and his predecessors conformed to a standard pattern from which Tacitus departed. It is true that Livy in Books 21-45 employs a regular internal–external–internal pattern based on the consuls’ movements between Rome and their provinces, with copious details on routine matters in the opening and closing domestic sections. However, Livy manipulates this framework freely for his own purposes, especially when incorporating Polybian material. Moreover, the pattern is characteristic only of his account of the Middle Republic: the annual narratives of Books do not conform to it, and Livy probably abandoned it when dealing with events from the Social War on. It seems likely that the annual narratives of most of Livy’s predecessors were varied and informal, like those of Livy Books 1-10, and this is corroborated by fragments of Claudius Quadrigarius and Sallust’s Histories. Livy probably derived his mid-republican pattern from Valerius Antias: it will have been an innovatory feature of his work, based on documentary research, especially in the archives of the senate. Assessment of Tacitus’ handling of his annual narratives should take account of the wide range of models available to him within the annalistic tradition.Note: This paper was first published in Histos 1 (1997), and republished in a revised and abridged form in J. D. Chaplin and C. S. Kraus (eds), Oxford Readings in Classical Studies: Livy (Oxford, 2009), 118-47. The present version reproduces the original paper in full, but incorporates the 2009 revisions and a few further changes.